Pengembangan Jiwa Kewirausahaan/ Enterpreneurship di Kalangan Generasi Muda - Ella Safitri; Zuhrinal Nawawi (Universitas Muhammadiyah Enrekang, 2022)
The entrepreneurial spirit is very important and very much needed to be contained in the personality of the younger generation. Because this will greatly affect the quality and state of the Indonesian economy in the future. Entrepreneurship will be very helpful in suppressing and reducing the unemployment rate in Indonesia because the output generated from entrepreneurial activities will open and generate new jobs.